lncRNA LINC01296 Promotes Oral Squamous Cell Carcinoma Development by Binding with SRSF1 - Zhang, Yanhui (Biomed Res Int, 2021)
OBJECTIVE: Oral squamous cell carcinoma (OSCC) is the most common malignant tumor of the head and neck, with strong local invasiveness and cervical lymph node metastasis. The purpose of this study was to investigate the role of LINC01296 in oral squamous cell carcinoma and its possible mechanism. MATERIALS AND METHODS: GEPAI database analysis and clinical samples were used to detect the expression of LINC01296 in head and neck cancer. In vivo experiment, MTT, clone formation assay, and transwell were used to detect the proliferation, migration, and invasion of oral squamous cell carcinoma. The effect of LINC01296 on EMT was detected by western blot and qRT-PCR to measure the expression of epithelial and mesenchymal phenotypic markers. BALB/c nude mice were used to carry out in vitro treatment experiment. In terms of mechanism, the binding relationship between LINC01296 and SRSF1 was predicted and verified by the RBPDB database and RNA pull-down assay. RESULTS: LINC01296 was highly expressed in clinical samples and cell lines of oral squamous cell carcinoma. Overexpression of LINC01296 promoted the proliferation, invasion, and migration of oral squamous cell carcinoma cells and accelerated the formation of xenografts, while silencing LINC01296 inhibited tumor progression. In mechanism, LINC01296 plays a tumor-promoting role by binding to SRSF1 protein. CONCLUSION: LINC01296 promotes malignant lesions in oral squamous cell carcinoma by binding to SRSF1 protein, which provides important experimental data and theoretical basis for the prevention, diagnosis, and treatment of oral squamous cell carcinoma.